Mengukur Efisiensi Teknis dan Pendapatan Petani Jagung MDR-3 di Pulau Madura (Measuring Technical Efficiency and Farmers’ Income of MDR-3 Maize in Madura Island)) - HAYATI, MARDIYAH; Taufik Rizal Dwi Adi Nugroho; Mohammad Wahyu Firdaus (JURNAL PANGAN, 2024)
Benih jagung unggul MDR-3 sebagai inovasi dari perusahaan lokal Madura diharapkan menjadi salah satu solusi menyelesaikan permasalahan rendahnya produktivitas jagung di Pulau Madura. Tujuan penelitian ini adalah untuk mengetahui tingkat efisiensi teknis usahatani jagung dan mengetahui tingkat pendapatan usahatani jagung MDR-3. Total responden adalah 70 petani yang tersebar di Kabupaten Pamekasan dan Sumenep dan dipilih secara purposive. Kegiatan usahatani jagung MDR-3 tergolong efisien secara teknis dengan nilai Technical Efficiency 0,887. Tingkat pendapatan usahatani jagung MDR-3 adalah Rp10.536.894,00 dengan nilai R/C rasio berada pada angka 3,8. Hasil penelitian membuktikan penggunaan benih jagung varietas unggul MDR-3 pada kegiatan usahatani tergolong efisien dan memberikan kontribusi pendapatan yang lebih tinggi daripada penggunaan benih jagung lokal dan lebih tinggi dari tingkat Upah Minimum Kabupaten/Kota (UMK).   MDR-3 maize seeds, as an innovation from local companies in Madura, are expected to solve the problem of low maize productivity on Madura Island. This study aimed to determine the technical efficiency of maize farming using a stochastic production function assisted by the frontier 4.1c application and to determine the income level of MDR-3 maize farming. Seventy farmers from Pamekasan and Sumenep Regencies were selected purposely. MDR-3 maize farming activities were classified as technically efficient with a Technical Efficiency value of 0.887. The income level of MDR-3 maize farming was Rp10,536,894,00 with an R/C ratio of 3.8. The results of this study empirically prove that the use of MDR-3 superior maize seeds in farming activities is classified as efficient and provides a higher income contribution than the use of local maize seeds and is higher than the minimum wage level of the regency/city (UMK) at the research location.